Perfect mode locking of solid-state lasers by a double passive modulation - Martinez, Oscar Eduardo, author; Marconi, Mario Carlos, author; Diodati, F. P., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1982)
A new configuration, which incorporates a second passive modulation, has permitted complete selectivity in passive mode locking of solid-state lasers. A theoretical study is presented showing the existence of qualitatively different types of emission depending on the parameters of the system. Computed simulations are made to show the dependence of the emission on such parameters, and are used to determine their optimum range. Experimental results are presented confirming computed predictions.
Keywords: solid state lasers; mode locking; modulation; configuration; mathematical models; parametric analysis; simulation; optimization